A novel variable antibody fragment dimerized by leucine zippers with enhanced neutralizing potency against rabies virus G protein compared to its corresponding single-chain variable antibody fragment. Issue 2 (December 2015) - Li, Zhuang; Cheng, Yue; Xi, Hualong; Gu, Tiejun; Yuan, Ruosen; Chen, Xiaoxu; Jiang, Chunlai; Kong, Wei; Wu, Yongge
Highlights: The VH and VL interact to form zipFv with the aid of Fos and Jun zippers leading to enhanced affinity, stability and neutralizing potency in comparison with scFv, which might enlighten the readers focusing on study of dimerizing VH and VL and even other protein molecules. The assembly pattern of VH and VL in zipFv is identical as that of its parent IgG resulting in similar protective rate as rabies immunoglobulin (RIG) in mice challenged with a lethal dose of RV, so zipFv may replace the current use of RIG in the post-exposure prophylaxis against rabies infection, with many advantages especially the low cost and high safety compared with monoclonal antibody. Cysteines are added in zipFv for new disulfide-bonds linking the VH and VL to enhance the stability. The interchain disulfide-bonds can also allow zipFv to remain as a heterodimer in non-reducing and denaturing conditions to facilitate detection, which might arouse the readers' interests on study of molecular modification method. Abstract: Fatal rabies can be prevented effectively by post-exposure prophylactic (PEP) with rabies immunoglobulin (RIG). Single-chain variable fragments (scFv), which are composed of a variable heavy chain (VH ) and a variable light chain (VL ) connected by a peptide linker, can potentially be used to replace RIG. However, in our previous study, a scFv (scFV57S) specific for the rabies virus (RV) G protein showed a lower neutralizing potency than that of its parent IgG due to lower stability and altered peptide assembly pattern. In monoclonal antibodies, the VH and VL interact non-covalently, while in scFvs the VH is connected covalently with the VL by the artificial linker. In this study, we constructed and expressed two peptides 57VL -JUN-HIS and 57VH -FOS-HA in Escherichia coli . The well-known Fos and Jun leucine zippers were utilized to dimerize VH and VL similarly to the IgG counterpart. The two peptides assembled to form zipFv57S in vitro . Due to the greater similarity in structure with IgG, the zipFv57S protein showed a higher binding ability and affinity resulting in notable improvement of in vitro neutralizing activity over its corresponding scFv. The zipFv57S protein was also found to be more stable and showed similar protective rate as RIG in mice challenged with a lethal dose of RV. Our results not only indicated zipFv57S as an ideal alternative for RIG in PEP but also offered a novel and efficient hetero-dimerization pattern of VH and VL leading to enhanced neutralizing potency.